ANALISIS PERTIMBANGAN HAKIM DALAM TINDAK PIDANA PEMBUNUHAN TERHADAP ANAK PADA PERKARA NOMOR 56/Pid.B/2019/PN.LB - Novia Astuti; Erry Gusman; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Abstract: Child is someone who is not yet 18 years old, including children who are still in the womb. Children are dignity as whole human beings, children as shoots, potentials and young generations to succeed the nation's ideals have a strategic role and have special characteristics and characteristics that guarantee the continuity of the extension of the nation and state in the future so that every child will be able to assume this responsibility, it is necessary get the widest possible opportunity for the body and develop optimally both physically and mentally and socially. Protection of children in a nation's society is a measure of the nation's civilization, therefore it must be endeavored according to the capabilities of the nation and the nation. Therefore, there is a need for legal guarantees for child protection activities. Legal certainty needs to be sought for the sake of continuing child protection activities and preventing abuses that bring unwanted negative consequences in the implementation of child protection activities. Not infrequently children become victims of crime, one of which becomes a victim of murder. This shows the weak position of the child when experiencing self-defense and the child being very vulnerable to violence so that it can take the child's life which is carried out by those around him. The purpose of this study is to find out and understand how the judge considers the crime of killing a child in case number 56/Pid.B/2019/PN Lb and the application of sanctions to the perpetrators of the crime of murdering children in case number 56/Pid.B /2019/PN Lb. The method used is the normative legal research method where this method is a legal research method that is only shown in written regulations so that this research is very closely related to the library because it will require library data.Keywords: Judgment considerations, Murder, towards children.